Clinical Characteristics of Pelvic Organ Prolapse at a Nationally Referred General Hospital: A Retrospective Study (2023-2024) - Djusad, Suskhan; Hakim, Surahman; Meutia, Alfa Putri; Priyatini, Tyas; Moegni, Fernandi; Hidayah, Gita Nurul; Azzahra, Kayla Rianna (Indonesian Socety of Obstetrics and Gynecology, 2025)
AbstractObjective: To evaluate the clinical characteristics of patients with Pelvic Organ Prolapse (POP) in national referral hospitals and analyze the relationship between age, parity, and prolapse severity. Methods: This medical record–based retrospective study included 353 POP patients from 2023–2024. Variables assessed were age, parity, prolapse severity (POP-Q), sexual activity status, and type of therapy received. Correlation analysis was performed using Spearman’s rank correlation with SPSS version 26. Results: Most patients (81.3%) were postmenopausal, and 64.6% were multiparous. The majority presented with stage IV prolapse (34.8%), and operative therapy was the primary treatment choice (89.5%). Significant associations were observed between age and prolapse severity (? = 0.208, p < 0.001) and between parity and prolapse severity (? = 0.215, p < 0.001). These findings indicate that increasing age and higher parity are significantly associated with more severe POP, although the correlation strength was weak. Conclusions: POP was most commonly found in postmenopausal women, with higher severity among older and multiparous patients. These findings highlight the importance of early screening and preventive strategies to reduce POP progression. Further prospective multicenter studies are needed to evaluate the long-term impact of POP on quality of life and to compare the effectiveness of conservative versus operative therapies. Keywords: conservative therapy, degree of prolapse, parity, Pelvic Organ Prolapse, reproductive age, surgical intervention.